First 12-month follow-up of bioresorbable synthetic heart valves implanted in the aortic position in sheep. (3rd October 2022) - Vis, A; De Kort, B J; Szymczyk, W; Van Rijswijk, J W; Dekker, S; Driessen, R; Wijkstra, N; Grundeman, P F; Niessen, H W M; Janssen, H M; Dankers, P Y W; Smits, A I P M; et al.
Abstract: Background: Replacement of diseased heart valves with the currently available valve prostheses has serious drawbacks. The use of bioresorbable synthetic "in situ tissue engineered" heart valve prostheses has been proposed to overcome the limitations of traditional heart valve prostheses. Such bioresorbable synthetic heart valve prostheses have been successfully tested as pulmonary valve replacements in preclinical studies, but data on aortic valve replacement is lacking. Here, we present the first in-vivo study on the long-term functionality of bioresorbable synthetic heart valves in the high-pressure circulation. Methods: Approval for the animal studies was obtained by the Amsterdam University Medical Centres Animal Care Ethics Committee (AVD1180020197705) and are in agreement with the current Dutch law on animal experiments (WOD). We surgically implanted bioresorbable synthetic aortic valve prostheses in 20 female Swifter sheep in orthotopic position. The scheduled follow-up times were 1, 3, 6, 9 and 12 months. Results: Fifteen sheep (75%) recovered well from the surgical valve implantation procedure and were included in this analysis. No sheep died due to valve failure. All valves remained free from active infectious endocarditis, thrombotic complications, and pathological calcification. A total of 10 valves (67%) were intact, thin and pliable and remained free from leaflet thickening, retraction and degradation up to 12 months after implantation. In most valves (67%), the scaffold remained sparsely- or unpopulated by cells during 12 months follow up. In some valves (33%), colonization of the valve scaffold was observed, however this was most often associated with partial degradation of the leaflet and leaflet thickening. In general, the degradation of the scaffold fibres was limited throughout the follow-up period. Conclusion: We are the first to evaluate in vivo bioresorbable synthetic heart valves in aortic position. While valves remained functional, the study also serves as a starting point to further optimize scaffold and neotissue development for heart valve replacement in the high-pressure environment. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1. Cardiovasculair Onderzoek Nederland (grant number CVON2012-01)2. Netherlands Organization for Scientific Research (024.003.013)